Seasonal Photosynthesis, Respiration, and Calcification of a Temperate Maërl Bed in Southern Portugal - Sordo, Laura; Santos, Rui; Barrote, Isabel; Freitas, Cátia; Silva, João (Frontiers in Marine Science, 2020)
Rhodolith (maërl) beds are biodiversity hotspots with a worldwide distribution. Maërl is the general term for free-living non-geniculate rhodoliths or coralline red algae. In southern Portugal, maërl beds are mainly composed by Phymatolithon lusitanicum, recently identified as a new species and commonly misidentified as Phymatolithon calcareum. Photosynthesis, respiration and growth rates of the algae were measured seasonally, as well as the photosynthetic pigment composition. To characterize the seasonal and interannual patterns of key abiotic conditions in the largest described maërl bed of the Portuguese coast, temperature, irradiance and dissolved oxygen were continuously monitored over a two-year period. At the bed depth (22 meters), temperature ranged between 14 ºC in winter and 24 ºC in summer, irradiance varied from 5 to 75 μmol m-2 s-1 and dissolved oxygen from 5.8 to 7.25 mgO2 L-1. We found a strong linear relationship (r2=0.95) between gross primary production (GPP) and relative electron transport rates (rETR). Both methods led to similar results and an average molar ratio of 0.24. Photosynthesis and respiration increased in summer and decreased in autumn and winter. In the summer of 2013 the growth rates where two fold higher (1.34 µmol CaCO3 g-1day-1) than in the other seasons. In winter and spring, to compensate for light deprivation and low temperature, algae increased their chlorophyll a and carotenoid concentrations while also decreasing their phycobilin concentration, in this case probably due to nutrient limitation. To isolate the role of temperature on the algae’s metabolism, the photosynthetic and respiration rates of individual thalli were measured at 8 different temperatures in the laboratory (from 12 to 26 ºC). Phymatolithon lusitanicum photosynthesis increased 2-fold after a threshold of 18 ºC (from 2.2 at 18 °C to 3.87 µmol O2 m-2 s-1 at 20 °C), whereas respiration increased 4-fold with temperature after a threshold of 22 º C (from -0.38 at 18 °C to -1.81 µmol O2 m-2 s-1 at 24 °C). The significant increases on respiration, photosynthetic rates and maximum growth with temperature reveal that the metabolic rates of P. lusitanicum are highly sensitive to ocean warming.